Using digital platforms in pre-school education: benefits, challenges and perceptions of teachers and parents - Cireașă (Bosoi), Ioana-Theodora (Technium Education and Humanities, 2025)
In the context of accelerated digitalization and educational innovation, the integration of digital platforms in early childhood education has become both a necessity and a challenge. The present study investigates teachers' and parents' perceptions of the use of digital platforms in the Romanian pre-school system, focusing on their impact on children's learning, engagement and development. Using a mixed methodological approach, quantitative data were collected through questionnaires (N=150) and qualitative data through semi-structured interviews and direct observation. The results reveal a generally positive attitude towards digital tools, with acknowledged benefits in terms of motivation, personalization of learning and communication. However, there are significant concerns about screen time, technical difficulties and the need for training. The study underlines the importance of a balanced and pedagogically informed use of digital platforms and provides practical recommendations for their integration in early childhood education.